Impact of cuddler service-learning program in medical student education of opioid use disorder in pregnancy and neonatal opioid withdrawal syndrome. Issue 4 (2nd October 2021) - Gummadi, Nina H.; D'Amico, Maria; Chandra, Phanirekha; Krumholz, Julia O.; Mumber, Hannah E.; Hoyo, Leonie; Miller, Melissa; Borba, Christina P.; Wachman, Elisha M.
Abstract: Background: Given the increasing incidence of neonatal opioid withdrawal syndrome (NOWS), medical student training on substance use disorders (SUDs) and opioid use disorder (OUD) in pregnancy must be augmented. Through the Cuddling Assists in Lowering Maternal and Infant Stress (CALM) service-learning program, medical students attend SUD-related didactics and provide monthly cuddling services to infants with NOWS. Objective: This study examines the impact of CALM on medical students' attitudes toward individuals with SUDs and self-reported comfort with clinical skills related to caring for this population. Methods: Self-reported pre- and post-survey data was collected at the beginning and end of an academic year from the intervention group, CALM cuddlers, and the control group, non-cuddlers for 2 years. Mean total survey scores and individual survey questions using a 3-point Likert scale were compared before and after 1 year of participation for cuddlers and for non-cuddlers using paired t-tests and two sample t-tests. Results: The mean total score increased for cuddlers after participation in the intervention (MD 0.13, SD 0.26, p = 0.03). Mean scores for the comfort-related subset of questions also increased significantly for cuddlers after participation in the intervention (MD 0.22, SD 0.41, p = 0.01). Cuddlers felt more comfortable discussing substance use with appropriate language (72.0% vs 51.5%, p = 0.03), talking with patients about substance use (72.0% vs 36.0%, p = 0.01), and asking about substance use or recovery (80.0% vs 48.0%, p = 0.01). Conclusion: OUD- and NOWS-related service-learning positively impacts student attitudes and self-reported comfort with skills related to caring for individuals with SUDs, such as communicating about substance use.